EFFECT OF FLUID VISCOSITY ON FLUIDIZATION HYDRODYNAMICS AN EXPERIMENTAL AND COMPARATIVE STUDY - KECHROUD, Nassima; TIGHZERT, Hamid (Studia Universitatis Babeș-Bolyai Chemia, 2026)
In this study, we conducted an experimental investigation of the fluidization behavior of spherical glass particles with diameters dp=2 mm and dp=4 mm, using Newtonian fluids (aqueous sugar solutions). The influence of fluid viscosity on key global hydrodynamic characteristics of fluidization was examined, including the minimum fluidization velocity, the terminal settling velocity of the particles, and bed expansion. Experiments were carried out in a cylindrical glass column with an inner diameter of D=20 mm and a height of H=1500 mm. The minimum fluidization velocity and bed expansion were determined experimentally for different solid–liquid systems. The experimental results were compared with various correlations from the literature. It was found that the results are in good agreement with some of these correlations, particularly for bed porosity values below 0.6.